CRITICAL THINKING ASPECT OF SUCCESSFUL ENGLISH LEARNERS IN THE 21ST CENTURY AT SENIOR HIGH SCHOOL - Aan Roihatul Jannah; Farouk Imam Arrasyid; Ahmad Rifai (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2021)
the learners’ skills of communication, collaboration, creative and critical thinking, information literacy, media literacy, technology literacy, leadership, initiative, productivity, social skill and flexibility are the important requirements in this 21st century. Those skills can be developed through learning a foreign language. A successful language learner covers several characteristics, which quite similar with the characteristics of a bilingual or multilingual. A lot of research had explored the characteristics of a successful language learner, without specifying the skills involved. The aim of this research is to analyze the profile of successful English learners on their critical thinking aspect. The method of this research is qualitative and the data is collected through interview for both teacher and learners. The result shows that the successful learners are commonly reached the standard of a good critical thinking based on the the theory adapted.